Assessment of passive musculoarticular ankle stiffness in children, adolescents and young adults with haemophilic ankle arthropathy. Issue 3 (30th March 2018) - Lobet, S.; Cartiaux, O.; Peerlinck, K.; Henrard, S.; Hermans, C.; Detrembleur, C.; Deschamps, K.
Abstract : Objectives: To measure passive musculoarticular ankle stiffness (PMAAS) and its intra‐ and interday reliability in adult control subjects without ankle disorders. We also sought to quantify PMAAS in children, adolescents and young adults with haemophilia (CAAwH) taking into account the accurate tibiotalar and subtalar joints structural status obtained by magnetic resonance imaging (MRI). Methods: We included 23 CAAwH and 23 typically developing boys (TDB) matched by age, weight and height, along with 25 healthy volunteers for reliability assessment. All CAAwH underwent bilateral ankle MRI, with anatomical status assessed using the International Prophylaxis Study Group MRI scale. All CAAwH underwent PMAAS testing for both sides randomly vs the dominant side (DS) in TDBs. For assessing viscous stiffness (VS) and elastic stiffness (ES), eight different oscillation frequencies were randomly repeated three times for each subject. Results: Good‐to‐excellent intra‐ and interday reliability was observed for ES and VS variables. No relevant differences were observed between the ankle viscoelastic properties in CAAwH without joint damage and matched TDBs, whereas the study revealed significantly increased ES in the affected ankles of CAAwH with severe unilateral joint involvement compared to the non‐affected joint. Conclusion: This study confirmed increased ES in the severely affected ankles of CAAwH compared to non‐affected sides. No differences in the ankle viscoelastic properties of CAAwH with or without joint damage were observed, however, compared to matched TDB.